Analisis Perbedaan Kinerja Saham Emiten Subsektor Transportasi di Masa Sebelum dan Semasa Pandemi Covid-19 - Pebriyanti, Ni Kadek Melina; Gayatri, Gayatri (E-Jurnal Akuntansi, 2023)
This research aims to analyze differences in stock performance of issuers in the transportation subsector before and during the Covid-19 pandemic. The sample was determined using a nonprobability sampling method with a purposive sampling technique on transport subsector issuers listed on the Indonesia Stock Exchange (BEI) as of March 2020. The analytical tools used were Partial Least Square (PLS) and the Wilcoxon Signed Rank Test. The findings show that the current ratio and debt to equity ratio have no effect on stock performance. Total assets turnover and return on assets have a significant positive influence on stock performance. In the difference analysis, the result was that the value of Asymp.Sig. (2-tailed), namely 0.274 > ? = 0.050, meaning there is no difference in the performance of shares of issuers in the transportation subsector before and during the Covid-19 pandemic. Keywords: Financial performances; Stock performances; Covid-19.